2022
DOI: 10.1002/chem.202202748
|View full text |Cite
|
Sign up to set email alerts
|

A Stereodivergent Approach to the Synthesis of gem‐Diborylcyclopropanes

Abstract: We report a designed stereodivergent strategy for the synthesis of gem‐diborylcyclopropanes. The reaction provides a highly modular approach to prepare cyclopropane ring variants bearing gem‐(Bpin,Bpin), gem‐(Bpin,Bdan), and gem‐(Bpin,BF3K), with outstanding levels of stereocontrol. This was achieved by diastereoselective Pd‐catalyzed cyclopropanation reactions of gem‐diborylalkenes with α‐diazoarylacetates and α‐diazoaryl‐trifluoromethyl. The key to the success of this general protocol was the diastereoselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…We obtained the desired mixed gem -diborylated cycloaddition products 10 and 11 respectively in good yield as described in Fig. 5g 25 , 60 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We obtained the desired mixed gem -diborylated cycloaddition products 10 and 11 respectively in good yield as described in Fig. 5g 25 , 60 .…”
Section: Resultsmentioning
confidence: 97%
“…3b . Notably, having this mixed (Bpin,Bdan) unit not only will give the flexibility to tune the reactivity of the boron groups, but also might influence the reactivity of the double bond in alkene-Bdan 2 25 , 60 , 61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 , 19b , 19c , 20 ] We hypothesized that the preparation of β‐keto‐( gem ‐di)borylalkane via the planned photoredox‐mediated deoxygenated approach[ 2g , 2h , 2i , 10 , 11b ] would be particularly appealing due to the versatility of the carbonyl group, as well as the α‐position to carbonyl and the boryl units, which can be converted to other carbon motifs via modular and programmed transformations (Figure 1 E). [ 14 , 18 , 21 ] However, although several approaches to photo‐activated vinyl boronic esters have been reported,[ 12 , 13 , 16 ] it was unclear whether vinyl boronic esters, for example, 2 , 2 ’ would participate in the proposed photoredox‐mediated deoxygenative transformation, since the boron groups might undergo a sort of complexation with the triphenylphosphine (PPh3), which might prevent this transformation from occurring. However, 11 B NMR and 31 P NMR studies revealed no complexation between the B‐groups and the PPh3 (please see the Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…Although applying gem ‐diborylakenes with other boryl groups (i. e., not Bpin group) were unsuccessful, we were alternatively able to convert to the gem ‐(Bpin, Bpin) product for example, 3 a into gem ‐(Bpin, BF3Cs) salt 3 a ‐ BF3 through a selective trifluorination reaction. [ 13 , 21 ]…”
Section: Resultsmentioning
confidence: 99%